2019
DOI: 10.1096/fj.201801627rrr
|View full text |Cite
|
Sign up to set email alerts
|

Host genetics and diet composition interact to modulate gut microbiota and predisposition to metabolic syndrome in spontaneously hypertensive stroke‐prone rats

Abstract: Metabolic syndrome encompasses obesity, glucose intolerance, hypertension, and dyslipidemia; however, the interactions between diet and host physiology that predispose to metabolic syndrome are incompletely understood. Here, we explored the effects of a high‐fat diet (HFD) on energy balance, gut microbiota, and risk factors of metabolic syndrome in spontaneously hypertensive stroke‐prone (SHRSP) and Wistar‐Kyoto (WKY) rats. We found that the SHRSP rats were hypertensive, hyperphagic, less sensitive to hypophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…In a separate cohort of chow‐fed rats (n = 6/group), the volume of oxygen consumed (VO2, mL/kg body weight/h) and carbon dioxide produced (VCO2, mL/kg body weight/h) were continuously recorded at 12‐minutes intervals by indirect calorimetry (CLAMS setup; 2‐L/min flow) following a previously published protocol 111 . The total energy expenditure was computed using the following equation: 3.815 × VO2 (L/h) + 1.232 × VCO2 (L/h), and data were represented as kcal/h.…”
Section: Methodsmentioning
confidence: 99%
“…In a separate cohort of chow‐fed rats (n = 6/group), the volume of oxygen consumed (VO2, mL/kg body weight/h) and carbon dioxide produced (VCO2, mL/kg body weight/h) were continuously recorded at 12‐minutes intervals by indirect calorimetry (CLAMS setup; 2‐L/min flow) following a previously published protocol 111 . The total energy expenditure was computed using the following equation: 3.815 × VO2 (L/h) + 1.232 × VCO2 (L/h), and data were represented as kcal/h.…”
Section: Methodsmentioning
confidence: 99%
“…Except for affording more energy, it was found that a high-fat diet diminished gut barrier-protecting bacteria and enriched endotoxin producers (Chassaing et al, 2015) to induce lipid accumulation (Faillaci et al, 2018). Although the intestinal microbiota is influenced by diet components, there is a substantial interindividual variation in the intestinal bacterial composition in response to diets, suggesting the genetic factor should not be ignored when we evaluate the metabolic characteristics (Ussar et al, 2016;Singh et al, 2019). Kreznar et al (2017) characterized the metabolic phenotypes of eight genetically distinct inbred mouse strains in response to a high energy diet and found that different mouse strains showed great variation in the intestinal microbiota as well as the diabetesrelated phenotypes, showing the dominant role of genetic factors in shaping the intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal (gut) microbiota is an important environmental factor that plays a key role in development of obesity and diabetes . The trillions of microbes present in the intestinal tract form a complex system, and physiological state is modulated by interactions between microbiota and the host .…”
Section: Introductionmentioning
confidence: 99%
“…3,4 The trillions of microbes present in the intestinal tract form a complex system, and physiological state is modulated by interactions between microbiota and the host. 3,4 The trillions of microbes present in the intestinal tract form a complex system, and physiological state is modulated by interactions between microbiota and the host.…”
mentioning
confidence: 99%